Exploring the Role of Female Successor “’Amrah bint ’Abd al-Raḥmān” in Narration of Prophetic Traditions - Musferah Mehfooz; Razia Shabana (Journal of Islamic and Religious Studies, 2019)
Although several studies have investigated the contribution of Muslim women about their lives and works in large corpus of the ḥadīth sciences until now, but much are needed to be explored. Doubtlessly 'Amrah bint 'Abd al-Raḥmān had contributed to the large corpus of the ḥadīth sciences and also the core of Islamic knowledge parallel to her male counterparts. By highlighting her efforts for learning and her struggle for transmission of fundamental text, reveals how a female successor acquired exemplary reputations in her era. Particularly, her rich insight, deep knowledge in ḥadīth sciences and exemplary piety attracted students and placed parallel to her male counterparts in Islamic knowledge of her time. In sum, this study not merely sheds light upon the prolific contribution of an eminent female successor 'Amrah bint 'Abd al-Raḥmān in ḥadīth narrations, but argues that these scholarly females should be given more credit for being interacting educators and not just transmitters. Doubtlewssly, the study would be helpful to revise our understandings of Islamic knowledge during early period of Islam regarding gendered dynamics and their great contribution to dissemination and transmission of classical text and Islamic knowledge.